The Effect of Quality of Work Life, Hardiness and Perceived of Alternative Job Opportunities on Turnover Intentions - Ira Setyawati (Bina Nusantara University, 2021)
Many behaviors that indicate turnover intentions in the company become a serious problem such as laziness to work, high absences, many employees do not renew their contracts, employee dissatisfaction with the company policies, high-level work stress, etc. This study aimed to examine the influence of quality of work life, hardiness, and perceived of alternative job opportunities on turnover intentions. This study method used is a quantitative method with the type of associative research. Data collection with questionnaire scale and sample of 167 employees. Data analysis uses multiple linear regression using SPSS version 26 for Windows software. This study found that quality of work life, hardiness, and perceived of alternative job opportunities together influenced turnover intentions by 57.8%. This study also provides an overview for companies to consider the aspects that may affect turnover intentions. The company needs to consider the market situations before implementing the new policies, doing employee surveys to know their perceptions, and improve the company systems to create a good work environment.